Pemberdayaan Ideal Pada Masyarakat Sekitar Hutan Melalui Tanaman Kehidupan di Desa Sungai Ara Kabupaten Pelalawan - Syahrul Akmal Latif; Herman Herman Herman; Rosmita Rosmita (Jurnal Administrasi dan Kebijakan Publik, 2022)
The plant of life is a program prepared by the government through the regulation of the Minister of Environment and Forestry Number P.12/Menlhk-II/2015, for communities living around forests to be empowered by companies in accordance with these rules. The purpose of this study is to explain and provide recommendations on how to empower ideal communities around the forest through living plants in Sungai Ara Village, Pelalawan Regency. The method in this study is to use a qualitative method with a descriptive approach. This research was conducted in Sungai Ara Village, which is located in Pelalawan District, Pelalawan Regency, Riau Province. Data collection techniques were carried out by interviewing informants, the company and the community. The results in this study found that the ideal empowerment had not been implemented properly in Sungai Ara Village because empowerment was carried out by giving cash. Therefore, the authors recommend ideal empowerment by using concepts from various ideal theories and comparing the results of existing research. Recommendations are expected to create an ideal empowerment by involving all parties including the government, companies and the community itself